Physicochemical and isotopic (18O and 2H) characterization of the northern region of Tempisque aquifer, Costa Rica (UNED Research Journal, 2020)
Introduction: Groundwater resources supply 70% of drinking water in Costa Rica. Groundwater is in risk of pollution and overexploitation due to the lack of good management practices. There has been an increase in the number of wells registered in the Guanacaste area, particularly in the Tempisque aquifer. Objective: To investigate and generate new physicochemical and isotopic information (18O and 2H) to characterize the water resource of the northern region of the Tempisque aquifer. Methodology: We conducted four groundwater samplings in 12 groundwater wells between May 11 and November 12, 2010. We analyzed water samples to determine stable isotopes using off-axis integrated cavity output spectroscopy and also for physicochemical characterization. Results: We classified groundwater as hard and very hard water. The range of measured pH values was 6.57–7.91. The average conductivity in the study area was 437μS/cm. The range of bicarbonate concentrations was 129-342mg/L HCO3–. The groundwater in the northern region of the Tempisque aquifer is calcium bicarbonate and is characterized by an average temperature of 28.0°C. Conclusions: A decade ago, we found no groundwater contamination by metals neither evidence of saline intrusion. The aquifer recharge areas are at the same heights and some wells are characterized by meteorological recharges.
Keywords: Groundwater; pollution; stable isotopes; Tempisque; Guanacaste